OPTIMALISASI PENGGUNAAN SUMBERDAYA RUMAH TANGGA PETANI DI DAERAH ALIRAN SUNGAI (Kasus DAS Wawar, Kabupaten Kebumen dan Purworejo, Jawa Tengah) - Rachmat Hendayana (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2001)
The flood in the river basin area almost occur each years since 1980 and the inundation was affected not only the residence but also farming area (rice field and dry field). The objective of this study is to assess the optimization of household resources in the Wawar river basin area, Central Java in 1997/1998. The analysis conducted by using linear programming method. The research findings indicated: there are five patterns of farming system that results income optimization namely to cropping patern on Cisadane – IR 64 rice; IR 64 rice – red chili; watermelon in swam; area, and to take care chickens and fish. The outputs of those activities about 18.6 million rupiahs per year net income. For larger successful activities and farmers' optimization income in the Wawar river basin area, there are needed output price protection, capital support and technological breakthrough with managerial skill improvement of the farmer